2022
DOI: 10.1108/jpbm-02-2022-3855
|View full text |Cite
|
Sign up to set email alerts
|

How does involvement build loyalty towards music-streaming platforms? A multi-analytical SEM-ANN technique

Abstract: Purpose Given the acute competition between music-streaming platforms (MSPs), the purpose of this study is to identify the relational motivators of brand loyalty towards the MSP in terms of user-brand involvement, brand trust, brand engagement, brand recommendation and brand loyalty. Design/methodology/approach Cross-sectional quantitative data, gathered from a total of 340 eligible respondents via an online questionnaire survey, were empirically analysed and validated using a hybrid predictive-analytics str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 86 publications
0
12
0
1
Order By: Relevance
“…In addition, the convergent validity was assessed based on the AVE and since all AVE are greater than 0.50, we conclude that all constructs have good convergent validity (Leong et al. , 2011; Theadora et al. , 2023).…”
Section: Data Analysis and Resultsmentioning
confidence: 78%
See 1 more Smart Citation
“…In addition, the convergent validity was assessed based on the AVE and since all AVE are greater than 0.50, we conclude that all constructs have good convergent validity (Leong et al. , 2011; Theadora et al. , 2023).…”
Section: Data Analysis and Resultsmentioning
confidence: 78%
“…Table 7 shows that all of them are greater than 0.70 indicating that all constructs have good reliability (Adeline et al, 2023;Wong et al, 2023). In addition, the convergent validity was assessed based on the AVE and since all AVE are greater than 0.50, we conclude that all constructs have good convergent validity (Leong et al, 2011;Theadora et al, 2023). 8 shows that all square root of the AVE is greater than their respective correlation coefficients.…”
Section: Common Methods Bias (Cmb)mentioning
confidence: 87%
“…Consequently, we integrated PLS-SEM and ANNs to build a multi-analytical approach to accurately determine the most significant predictors of attitude and intention. Several studies [ 61 , 62 , 63 , 64 , 65 ] have highlighted the effectiveness of this multi-analytical approach in providing in-depth and accurate insights for decision-makers. These valuable insights should help decision-makers to make well-informed decisions for achieving their desired outcomes in the respective research domains.…”
Section: Resultsmentioning
confidence: 99%
“…Third, prior researchers have shown that consumers' behavioral intentions vary among social commerce platforms. Hence, future studies would benefit from comparing consumer attitudes and behaviors across specific social media or e‐commerce platforms (Dang et al, 2023; Theadora et al, 2022). Fifth, given the different influences and publicity of traditional and social media celebrities, future studies are suggested to adopt a comparative study of them as this study mainly focused on internet celebrities, thus providing comprehensive insights and guidance to social commerce sellers.…”
Section: Discussionmentioning
confidence: 99%